2008
DOI: 10.1530/rep-08-0134
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted secretory activation of the mammary gland after antenatal glucocorticoid treatment in sheep

Abstract: Antenatal glucocorticoids are administered to women at risk of preterm delivery to prevent neonatal respiratory morbidity. The effects of exogenous glucocorticoids on the development of lactation are unknown. This study investigated the effects of a single dose of antenatal glucocorticoids on secretory activation in sheep before and after parturition. Pregnant ewes (NZ36) were randomised to receive either medroxyprogesterone acetate (MPA) at 118 days of pregnancy and betamethasone at 125 days (BETA group), MPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
(25 reference statements)
1
11
1
Order By: Relevance
“…15,16,25 The present study found that PdG excretion in urine increased with advancing gestational age. Unlike our findings for plasma progesterone in sheep, 19 the present study did not find a sustained decrease in PdG concentration in urine after administration of betamethasone. This finding is consistent with other research in women.…”
Section: Excretion Of Pdgcontrasting
confidence: 99%
See 4 more Smart Citations
“…15,16,25 The present study found that PdG excretion in urine increased with advancing gestational age. Unlike our findings for plasma progesterone in sheep, 19 the present study did not find a sustained decrease in PdG concentration in urine after administration of betamethasone. This finding is consistent with other research in women.…”
Section: Excretion Of Pdgcontrasting
confidence: 99%
“…19 In contrast, increasing PdG excretion was positively associated with increasing lactose excretion as occurred with increasing gestational age. These findings suggest that advancing gestational age had a greater impact on the relationship between the concentrations of PdG and lactose in urine than the effect of betamethasone treatment in women.…”
Section: Excretion Of Lactosementioning
confidence: 87%
See 3 more Smart Citations